Membangkitkan Potensi Berpikir Kritis Menuju Kreativitas dengan Soal HOTS dan Inovasi Pembelajaran AI di Sekolah Islam Terpadu Raudhatul Ulum Sakatiga - Meryansumayeka, Meryansumayeka; Safitri, Erna Retna; Nuraeni, Zuli (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Higher Order Thinking Skills (HOTS) is one of the abilities that needs to be mastered by teachers and owned by students in dealing with daily life problems. In addition, research results show that the use of Artificial Intelligence (AI) can make a positive contribution to learning. However, in reality, students' HOTS in the partner school, SMPIT Raudhatul Ulum Sakatiga, is still low. This is because teachers have not fully understood and mastered the skills in designing learning and HOTS questions. This community service aims to improve teachers' knowledge and skills in developing HOTS questions and innovative learning with AI. Method: The method used includes several stages, namely location review, preparation, socialization, training, technology application, mentoring, evaluation, and follow-up. Results: The results showed that there was an increase of about 35% in the number of participants who understood HOTS and AI and an 85% increase in the number of participants who were able to use AI in developing HOTS lessons and questions. Conclusions: The success of this program is not only seen from the increase in students' critical thinking skills and creativity, but also from changes in learning methods that are more innovative and technology-based at SMPITRU Sakatiga.